Mitigasi Risiko Penyelenggaraan Lelang Eksekusi Hak Tanggungan pada Kantor Pelayanan Kekayaan Negara dan Lelang Padang - Ayu Fitriana (LPPM Universitas Ekasakti Padang, 2023)
A mortgage rights is a security right that is charged to land rights and objects related to land, as regulated in Law 4 of 1996 Concerning Mortgage Rights To Land And Objects Related To Land. Dependents guarantee the debtor's debt in the event that the debtor is unable to pay the debt or defaults. If this happens, the creditor can carry out the execution of the collateral object, requiring prior approval from the mortgagee and not through the fiat of the head of the court. The execution of the mortgage execution auction is regulated in Regulation of the Minister of Finance Number 213/PMK.06/2020 concerning Instructions for Conducting Auctions. In practice, auctions of mortgage objects that are carried out pose risks, one of which is legal risk. This is because many debtors are not willing to hand over objects that are used as collateral for collateral to be sold through auctions. The data the author uses comes from the Padang State Assets and Auction Service Office. The results and discussion show that 1. The execution of the mortgage execution auction at the vertical unit Office of State Assets Services and Auctions applies the E-Auction, or electronic auction system. E-Auctions. 2. Regarding the risks described above, risk mitigation can be carried out, such as: 1. Coordinate with the Legal and Information Section regarding the implementation of auctions that have the potential for legal problems, 2. Coordinate with banks so that they focus on priority scales of auction implementation and problem-free (free and clear) auctions, 3 Conduct education and communication related to implementation auction of execution of rights to banking stake holders and auction buyers, 4. Coordinate more intensively with the land office regarding the ease of administrative arrangements related to the execution of mortgage execution auctions.